¿Why Are Thre More Poor Women in Latin America? - Martínez Franzoni, Juliana (2018)
Latin America is emerging from a “left turn” or “Pink Tide” that started in 1998 and lasted through the mid-2010s. Electoral competition gave progressive platforms wider influence and highlighted demands for progressive labor and social policies. This shift to the left was the political outcome of citizens’ disillusionment with the unmet promises of earlier conservative governments. This disillusionment coincided with an economic boom. Although diverse, left-wing parties and their leaders voiced demands for change, especially in living conditions. By 2000, social outcomes and public policies advanced across the region.